Persepsi Remaja Terhadap Program Siaran Gade-gade’na Televisi Republik Indonesia (TVRI) di Sulawesi Selatan - Hasni Hasni; Pramudita Budi Rahayu (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2022)
This study aims to determine : 1) the perception of teenagers on local broadcast entertainment events, Gadegade’naTelevision of The Republic of Indonesia in South Sulawesi. 2) What factors influence youth perceptions of theGade-gade’na broadcast program on Television of the Republic of Indonesia, South Sulawesi. The type of research usedqualitative research with data collection techniques through interviews and documentation. Data analysis techniquesused data reduction, data presentation, and drawing conclusions. The result of the study stated that: 1) teenagers'perceptions of the Gade-gade’na broadcast program were categorized into perceptions based on the source and host,perceptions based on language style, and perceptions based on the content of the show. 2) Factors that influence youthperceptions of TVRI South Sulawesi’s Gade-gade’na broadcast program were internal factors and external factorsbecause internal factors had interest, the need for Gade-gade’na broadcast programs and literacy were also influentialbecause individuals were able to filter the information they accept. Then external factors, where there was an environment,experience, and communicators played an important role in receiving information.